The experiences of non-traditional students utilizing student support services: a qualitative study - Bannister, Stephanie J. (Kansas State University, 2009)
The purpose of this phenomenological study was to examine the impact of student support services on the engagement and satisfaction of undergraduate non-traditional students at Kansas State University. For the purposes of this study, student support services were defined as non-academic departments or offices providing support services to students. The research questions were: (1) How do the experiences of non-traditional students, when utilizing the services of university student support staff, impact their engagement and satisfaction? (2) How do non-traditional students regard their experiences with student support services at Kansas State University? (3) What types of programming do student support services at Kansas State University provide for non-traditional students? (4) What level of involvement with student support service functions do non-traditional students find as enhancing their learning experience? Following the completion of in-depth interviews of 20 non-traditional students, five student support staff members and observation of five student support staff offices, the researcher identified the emergence of six themes related to the engagement and satisfaction of non-traditional students: (1) commitment - student’s perceptions of efforts to engage and satisfy them through a commitment of university resources, (2) expectations - demonstration of investment in the students and validation of their presence on campus by communicating clear expectations, (3) support - provision and utilization of support services that promote student success (4) involvement - perceptions of the relationship between student and support staff and opportunities for academic and social integration, (5) learning - efforts to enhance the learning experiences of non-traditional students, (6) feedback – gathering of suggestions for change and improvement to the non-traditional student experience. These themes captured the experiences of non-traditional students while utilizing student support services. Students who develop or experience a positive connection with a student support staff member or faculty member reported that those experiences leave them feeling engaged in the life of the university and satisfied with their student role. Non-traditional students were confused about what student support services were available and how to utilize them. When students seek the help of support staff, the student often left feeling as though the staff do not understand their needs. Student support service offices did not differentiate between programs specifically for non-traditional and traditionally-aged students. Students could identify student support service staff as connectors as playing the role of; academic advisor, admissions representative, financial aid advisor, housing staff member, faculty member or others who take the opportunity to engage with the student.
Keywords: non-traditional students; student support services; Education, Higher (0745)